Case Report: Atezolizumab plus bevacizumab for combined hepatocellular-cholangiocarcinoma - Satake, Tomoyuki; Shibuki, Taro; Watanabe, Kazuo; Sasaki, Mitsuhito; Imaoka, Hiroshi; Mitsunaga, Shuichi; Kojima, Motohiro; Ikeda, Masafumi (Frontiers in Oncology, 2023)
Combined hepatocellular cholangiocarcinoma (cHCC-CCA) is a rare subtype of primary liver cancers. Therapeutic strategies for patients with cHCC-CCA are limited, and no standard systemic treatment has been established for unresectable cHCC-CCA. Here, we present six cases of cHCC-CCA treated with atezolizumab plus bevacizumab. We observed three partial responses and one stable disease as the best responses; two of these patients were still being treated with atezolizumab plus bevacizumab at the time of reporting (at least five months of treatment), whereas the remaining two patients were unable to continue treatment owing to adverse events. Atezolizumab plus bevacizumab may be an effective treatment for unresectable cHCC-CCA.